Post -Traumatic Stress Disorder Following Wars and Repression at Mosul City-Iraq - Mohammad Salih Khalaf Alkaisy; Salem Shehab Ahmed; Mahfoodh Sulaiman Alsydan; Ahmed Abdel Qader Suleiman; Nasir Muwfaq Younis; Mahmoud Mohammed Ahmed (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and Objectives: More than 27 years of wars, repression and sanction have led to humansuffering all over Iraq, this study was done to estimate the prevalence rates of symptoms of Post-traumaticstress disorder ,and estimating the rate of exposure to traumatic events in Mosul City / Iraq.Materials and Method: Across- sectional multi-cluster sample survey of 424 respondents aged 18 yearsor older, conducted at Mosul city from January to March 2019 . 159 households were surveyed. Posttraumaticstress disorder Symptoms and Trauma events measured by the Iraqi version of Harvard TraumaQuestionnaire.Results: During the past 27 years ( 97.96% ) of respondents experienced at least 4 traumatic events, (26.14%) experienced between 5-10 traumatic events and ( 17.51%) experienced more than 10 traumaticevents .The most common traumatic events experienced by respondents were home searching while theywere present , witnessing murder and murder of family members. The prevalence of respondents withsymptoms of Post-traumatic stress disorder der was (25.88%). Symptoms were more prevalent in womenthan in men with p value < 0.001 for PTSD.Conclusion: The findings of the study are concluded that the prevalence rate of symptoms of Post-traumaticstress disorder were high. This finding suggest the need for volunteer and health care planner.In addition tothe need for trained mental health care professionals.